Individuals with high bone mass have increased progression of radiographic and clinical features of knee osteoarthritis. Issue 9 (September 2020) - Hartley, A.; Hardcastle, S.A.; Paternoster, L.; McCloskey, E.; Poole, K.E.S.; Javaid, M.K.; Aye, M.; Moss, K.; Granell, R.; Gregory, J.; Williams, M.; Tobias, J.H.; et al.
Summary: Objective: High bone mass (HBM) is associated with an increased prevalence of radiographic knee OA (kOA), characterized by osteophytosis. We aimed to determine if progression of radiographic kOA, and its sub-phenotypes, is increased in HBM and whether observed changes are clinically relevant. Design: A cohort with and without HBM (L1 and/or total hip bone mineral density Z-score≥+3.2) had knee radiographs collected at baseline and 8-year follow-up. Sub-phenotypes were graded using the OARSI atlas. Medial/lateral tibial/femoral osteophyte and medial/lateral joint space narrowing (JSN) grades were summed and Δosteophytes, ΔJSN derived. Pain, function and stiffness were quantified using the WOMAC questionnaire. Associations between HBM status and sub-phenotype progression were determined using multivariable linear/poisson regression, adjusting for age, sex, height, baseline sub-phenotype grade, menopause, education and total body fat mass (TBFM). Generalized estimating equations accounted for individual-level clustering. Results: 169 individuals had repeated radiographs, providing 330 knee images; 63% had HBM, 73% were female, mean (SD) age was 58 (12) years. Whilst HBM was not clearly associated with overall Kellgren–Lawrence measured progression (RR = 1.55 [0.56.4.32]), HBM was positively associated with both Δosteophytes and ΔJSN individually (adjusted mean differences between individuals with and without HBM 0.45 [0.01.0.89] and 0.15 [0.01.0.29], respectively). HBM individuals had higher WOMAC knee pain scores ( β = 7.42 [1.17.13.66]), largely explained by adjustment for osteophyte score (58% attenuated) rather than JSN (30% attenuated) or TBFM (16% attenuated). The same pattern was observed for symptomatic stiffness and functional limitation. Conclusions: HBM is associated with osteophyte progression, which appears to contribute to increased reported pain, stiffness and functional loss.